The effects of shearing and ascorbyl palmitate administration on physiological and blood metabolite profile of Padjadjaran sheep under heat exposure treatment - Taofik, A.; Bandiati, S.; Maskoen, A. M.; Yusuf, M. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
Ascorbyl-6-palmitate (AP) was a lipid-soluble synthetic ester of ascorbic acid that has been used as a preservation agent for foods and as an antioxidant in cosmetics and related products. This study aims to investigate the effect of shearing management and ascorbyl palmitate administration on physiological and hematological profiles in under heat load Padjadjaran sheep. The physiological profile involves respiration rate (RR), Pulse rate (PR), and rectal temperature (RT). Twenty rams Padjadjaran 1 – 1,5 year-old, weighing between 25 to 47.5 kg used from sheep breeding station Purwakarta, West Java - Indonesia. There are two treatments level in this research, (1). Shearing divide into two groups, unshearing (c0) and shearing (c1); (2). AP administration also divides two groups, not given (a0) and given 400 mg each head daily (a1). The whole treatments were a0c0, a0c1, a1c0 and a1c1. Heat exposure application was exposed to sunlight when the sheep exposed, the animal tethered by rope at the neck region. The sheep exposed to the sun when the ambient temperature at least 34oC, 180 minutes each day, three days a week. The result showed that AP administration and shearing have interaction effects on RR, PR and RT. The level of glucose and total protein is affected by interaction effect of AP administration and shearing, while cholesterol affected to shearing. The conclusion, supplementing AP and shearing application could reduce the negative impact of heat stress on physiological and blood metabolite profiles of Padjadjaran sheep. Although the wool of local breed has not economic value, the shearing is regularly needed.